Futures markets, oil prices and the intertemporal approach to the current account - Elif C. Arbatli (Bank of Canada, 2008)
The intertemporal approach to the current account suggests modeling movements in the current account in a forward-looking, dynamic framework. In this framework, the current account reflects consumption smoothing of agents that lend and borrow from the rest of the world in the face of transitory shocks to income. As in permanent income models of consumption, the marginal propensity to consume out of transitory shocks is predicted to be significantly smaller which implies that a permanent income shock has a smaller effect on the current account than a transitory income shock. I use the term structure of petroleum futures to identify permanent and transitory innovations to petroleum prices. Then, I formulate a test of the intertemporal approach to the current account based on how a group of nineteen small petroleum exporters respond to each type of income shock. This market-based identification of income shocks and their perceived persistence offers a transparent framework for investigating the empirical evidence for the intertemporal approach. As the theory predicts, petroleum exporters have a significantly higher marginal propensity to consume out of permanent oil price shocks than out of transitory oil price shocks.
Keywords: C22; F21; F32; G13; 330; Balance of payments and components; Zahlungsbilanz; Termingeschäft; Financial Futures; Ölpreis; VAR-Modell